THE EFFECT OF ATMOSPHERE PRODUCT MIX AND STORE ON REPURCHASING INTEREST AT PRILLY CLOTHING STORE KOTA PEKANBARU - Lisna Diati; Lie Othman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study aims to determine the effect of product mix and store atmosphere on repurchase interest at Prilly Clothing Pekanbaru partially and simultaneously. In this study, the method used is a quantitative approach and uses analytical tools, namely SPSS version 23. The respondents in this study are consumers who make purchases at the Prilly Clothing Store as many as 99 respondents. Furthermore, the research results obtained are that there is a positive and significant effect between Product Mix (X1) and Repurchase Interest (Y), Store Atmosphire (X2) has a positive and significant effect on Repurchase Interest (Y), and Product Mix (X1) and Store Atmosphire (X2) has a positive and significant effect on Repurchase Interest (Y) at Prilly Clothing Stores in Pekanbaru City. Keywords: Product Mix, Store Atmosphire, and Repurchase Interest